Comparison of High‐Speed Optical Observations of a Lightning Flash From Space and the Ground. Issue 10 (7th October 2020) - van der Velde, Oscar A.; Montanyà, Joan; Neubert, Torsten; Chanrion, Olivier; Østgaard, Nikolai; Goodman, Steven; López, Jesús A.; Fabró, Ferran; Reglero, Victor
Abstract: We analyze a nighttime negative cloud‐to‐ground lightning flash in Colombia observed from the ground with a high‐speed camera at 5, 000 images per second and from space by the Atmosphere‐Space Interactions Monitor (ASIM) on the International Space Station (ISS), the Lightning Imaging Sensor also on the ISS (ISS‐LIS), and the Geostationary Lightning Mapper (GLM) on GOES‐16. The space instruments measure the oxygen band at 777.4 nm, allowing for direct comparisons of measurements, and the ground‐based camera observes in a wide visible band. After conversion to energy emitted at the cloud top, we find a good linear correspondence of the optical energies measured by the three space instruments, except that GLM values were 3 times higher. We attribute this mainly to the difference in viewing angles between spacecraft and the cloud. Over the entirety of the ASIM observed flash, optical pulses were detected by GLM and LIS, only when the energy reported by ASIM was greater than 332 J and 949 J, respectively. Their detection rate corresponds to 14% and 2.5%, respectively, of the flash duration observed by ASIM. The temporal variation of the high‐speed camera luminosity matched well the features observed by ASIM around the time of the stroke but reached ~3.9 times higher peak intensity during the return stroke, attributed to its broader spectral sensitivity band and a viewing angle advantage. Plain Language Summary: This paper describes the detection of the same lightning flash in Colombia by three different optical imaging systems monitoring lightning activity from space, as well as a high‐speed camera at the ground. Each space instrument (ASIM imager and photometer, ISS‐LIS, and GLM) has different characteristics, from the spacecraft orbit altitude to the detector spatial and temporal resolution. To make meaningful comparisons, we demonstrate how to calculate the optical energy emitted at the cloud top from the original luminosity values as received by each instrument. Then, reported cloud top energy and lightning detection efficiency for parts of the lightning flash duration are compared. The results show that during this flash, GLM detected only 14% of its total luminous activity as recorded by the sensitive ASIM photometer, and those features were reported 3 times more intense, most likely because of the different viewing angle to the storm. GLM detected a wider luminous cloud top area during the cloud‐to‐ground stroke than ASIM. The spatial resolution of the ASIM imager allows to identify cloud features also seen in GOES‐16 meteorological satellite images. Key Points: Lightning imagers on the ISS and GOES‐16 were compared quantitatively for one flash after conversion to energy emitted at the cloud top GLM reported 3 times higher energy than ASIM and detected 14% of the optical emissions registered by the ASIM photometer, ISS‐LIS 2.5% Light intensity curves of ASIM matched well with those recorded by a high‐speed camera at the ground around the time of a return stroke